Intraocular lens power calculation: Clinical comparison of 2 optical biometry devices - Rabsilber, Tanja Marina; Jepsen, Charlotte; Auffarth, Gerd U.; Holzer, Mike P. (Journal of cataract and refractive surgery, 2010)
PURPOSE: - To evaluate intraocular lens (IOL) power calculation using a new optical low-coherence reflectometry (OLCR) biometer and compare the results with those obtained with a partial coherence interferometry (PCI) optical biometer. - SETTING: - International Vision Correction Research Centre, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. - METHODS: - Biometry measurements in eyes of cataract patients were performed by the same examiner with an OLCR biometer (Lenstar LS 900/Allegro Biograph) and a PCI optical biometer (IOLMaster). After determination of axial length (AL), corneal radii values by keratometry (R1 and R2), and anterior chamber depth (ACD), power calculation for an AcrySof MA60AC IOL was compared between the 2 devices using 4 formulas and the corresponding IOL constants. The target was emmetropia. - RESULTS: - One hundred eyes of 100 cataract patients (mean age 70.0 years ± 10.6 [SD]) were measured. Of the biometry parameters, the only statistically significant differences between the 2 devices were in R2 (mean difference 0.02 ± 0.05 mm), (R1 + R2)/2 (mean difference 0.01 ± 0.04 mm), and ACD (mean difference 0.05 ± 0.11 mm) (P<.01, Wilcoxon test). The mean differences in IOL power calculations using the 4 formulas were not statistically significant between the 2 devices (P>.01, Wilcoxon test). - CONCLUSION: - The OLCR biometry device provided precise and valid measurements and thus can be used for the preoperative examination of cataract patients. - Financial Disclosure: - No author has a financial or proprietary interest in any material or method mentioned.